Reduced intravenous toxicity of amiodarone nanosuspension in mice and rats. (July 2013) - Barle, Ester Lovšin; Černe, Manica; Peternel, Luka; Homar, Miha
<x xml:space="preserve">Abstract</x> The toxicity of amiodarone Lek formulation (test formulation) was investigated after a single intravenous (i.v.) administration to mice and rats. When compared to the reference item, Cordarone (Cordarone®; Wyeth Pharmaceuticals Inc., Collegeville, Pennsylvania, USA), median lethal dose (LD50) after i.v. administration in female mice was 294.0 mg/kg body weight (b.w.) for the test formulation and 227.5 mg/kg b.w. for Cordarone. In female rats after i.v. administration, the LD50 value was 269.9 mg/kg b.w. for the test formulation and 192.4 mg/kg b.w. for Cordarone. By altering the particle size of amiodarone in the Lek formulation, we were able to improve the solubility of amiodarone, thereby decreasing the number and quantity of excipients needed for preparation of the i.v. formulation and, consequently, reduced the acute toxic effects observed in the present study.